Multi-objective methods for welding flux performance optimization (2010)
The traditional welding flux development is by lengthy and costly trial and error experiments and the optimum welding flux formulation is not guaranteed. This paper presents discussions on promising multi-objective decision making (MODM) methods that can mitigate the limitations of the traditional approach to welding flux design. The methods are weighted-sum scalarization (WSS), desirability indices, goal programming and compromise programming. The steps a welding flux designer (WFD) may follow to determine the best compromise welding flux, welding flux design situations where each may be useful and tradeoff explorations were mentioned. No attempt was made to determine the relative merits of the approaches because the usefulness of each depends on the welding flux design situation. The descriptions only serve as a guide for the WFD to decide which method best suits his needs.